Cause Analysis and Preventive Measures for Deterioration of Steam Turbine Lubricating Oil - Rikki Murtin; Liu Guoqing (Publikasi Indonesia, 2024)
Lubricating the oil system of the steam turbine in the power plant is an important part of maintaining the normal operation of a steam turbine. The quality of oil directly affects the safe and stable operation of steam turbines. If the oil quality deteriorates, it is very easy to cause major accidents such as wear of steam turbine bearings, jamming of the speed control system, and even burning of bearings, failure of steam turbine speed control system leading to overspeed. This research method uses a literature review. In the operation of the power plant, it is common for lubricating oil to exceed the standard particle size and water content, and there are many reasons for this. This article analyzes the causes of lubricating oil deterioration and explains more specific preventive measures. Conclusion Deterioration in oil quality and excessive particle size can easily lead to serious consequences. Therefore, it must be controlled from the inspection of new oil entering the factory, sampling and testing, and monitoring of the operation stage, to improve the maintenance process.